Transdural Anastomotic Aneurysm in Association with Moyamoya Disease: A Rare and Troublesome Neurosurgical Entity - Hou, Kun; Xu, Kan; Zhao, Yuhao; Yu, Jinlu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Moyamoya disease (MMD) is an idiopathic progressive steno-occlusive disease in the internal carotid artery (ICA) bifurcation. In rare circumstances, transdural anastomotic aneurysm (TAA) could develop during the progression of MMD. We present an illustrative case of TAA in association with MMD. To further explore this rare entity, a comprehensive literature review was also conducted. Our illustrative patient experienced spontaneous remission of the aneurysm during follow-up. By literature review, 12 patients with 13 TAAs, including our case, were identified. The patients aged from 10 to 74 years (46.3 ± 17.4). Eleven (92%) of the patients presented with intracranial hemorrhage, and 1 TAA (8%) was incidentally found. The responsible transdural collaterals were from the middle meningeal artery, occipital artery, internal maxillary artery, and ophthalmic artery in 8 (66.7%), 2 (16.7%), 1 (8%), and 2 (17%) patients, respectively. The anastomosed cerebral arteries were middle cerebral artery, anterior cerebral artery, posterior cerebral artery, and ICA in 5 (42%), 3 (25%), 3 (25%), and 1 (8%) patient, respectively. Eight (67%) patients underwent open surgeries. Two (17%) patients underwent transarterial embolization (TAE) only. Two (17%) patients experienced spontaneous remission of the aneurysm. Seven (58%) patients died or had neurologic deficits. TAAs rarely occur in the progression of MMD, which often presents with intracranial bleeding. Invasive management through open surgery or endovascular treatment is warranted to prevent catastrophic rebleeding. As some individuals might experience spontaneous aneurysm remission, conservative treatment and close imaging follow-up could be considered as an alternative when invasive treatment is risky.
Keywords: Moyamoya disease; Transdural collateral; Transdural anastomotic aneurysm; Subdural hematoma